Management of central airway obstruction: an American College of Chest Physicians clinical practice guideline - Mahmood, Kamran; Frazer-Green, Lindsy; Gonzalez, Anne V.; Shofer, Scott L.; Argento, Angela Christine; Welsby, Ian; Hales, Russell; Shojaee, Samira; Gardner, Donna D.; Chang, Joe Y.; Herth, Felix; Yarmus, Lonny (Chest, 2025)
Background - Central airway obstruction (CAO), seen in a variety of malignant and nonmalignant airway disorders, is associated with a poor prognosis. The management of CAO is dependent on provider training and local resources, which may make the clinical approach and outcomes highly variable. We reviewed the current literature and provided evidence-based recommendations for the management of CAO. - Methods - A multidisciplinary expert panel developed key questions using the Patient, Intervention, Comparator, and Outcomes format and conducted a systematic literature search using MEDLINE (PubMed) and the Cochrane Library. The panel screened references for inclusion and used vetted evaluation tools to assess the quality of included studies and extract data, and graded the level of evidence supporting each recommendation. A modified Delphi technique was used to reach consensus on recommendations. - Results - A total of 9,688 abstracts were reviewed, 150 full-text articles were assessed, and 31 studies were included in the analysis. One good practice statement and 10 graded recommendations were developed. The overall certainty of evidence was very low. - Conclusions - Therapeutic bronchoscopy can improve the symptoms, quality of life, and survival of patients with malignant and nonmalignant CAO. Multi-modality therapeutic options, including rigid bronchoscopy with general anesthesia, tumor/tissue debridement, ablation, dilation, and stent placement, should be utilized when appropriate. Therapeutic options and outcomes are dependent on the underlying etiology of CAO. A multidisciplinary approach and shared decision-making with the patient are strongly encouraged.
Online veröffentlicht: 18. Juli 2024
Gesehen am 02.10.2025